STRATEGI DIFERENSIASI DALAM PERENCANAAN PELAJARAN MATEMATIKA INKLUSIF UNTUK SISWA LAMBAT BELAJAR - Dian Nataria Oktaviani; Eka Puji Septiyani; Mohamad Aminudin (Universitas Islam Sultan Agung, 2025)
This research employs a qualitative case study method, also known as field research, which examines the process of differentiation learning in-depth in regular classes that include students with special needs (slow learners) in mathematics lessons. The subjects of this study were teachers and slow learners in the 4th grade of an Elementary School. The data in this study is information about teacher strategies in teaching mathematics in Grade 4. The results of this study are differentiation learning strategies in mathematics lessons in Grade 4 of Elementary School, seen from teacher skills in explaining mathematics lesson materials by accommodating all students' learning needs, including slow learners, both in terms of content and process differentiation, lesson planning according to students' learning needs, and providing feedback to students. Keywords: learning strategies, differentiation, slow learners, mathematics, special needs